Mermaid Construction A Compound-Predicate Construction with Biclausal Appearance - Tsunoda, Tasaku (Comparative Handbooks of Linguistics [CHL] ;, 2020)
This volume provides detailed studies of the crosslinguistically unusual mermaid construction in seventeen languages of Asia, including Modern Standard Japanese, and one language of Africa. This construction appears to be absent in languages of Europe, Oceania and the Americas. The name - mermaid construction - alludes to its paradoxical make-up, where the structure closely resembling a verb-predicate clause ends with what may look like a noun-predicate clause. Superficially it looks biclausal; however, syntactically it is monoclausal. It has a compound predicate which contains an independent noun, a clitic or an affix derived from a noun, or a nominalizer. Its compound predicate has a modal, evidential, aspectual, temporal, stylistic or discourse-related meaning. The paradox is resolved from a diachronic perspective insofar as a biclausal structure is reanalyzed as a monoclausal one. This volume shows how a noun may be reanalyzed to become a constituent of a predicate. It constitutes an important contribution to research on grammaticalization and in particular, the grammaticalization of nouns and more generally, to the typology of syntactic reanalysis.